2004
DOI: 10.1055/s-2004-832645
|View full text |Cite
|
Sign up to set email alerts
|

Polyacetylenic Compounds and Butanol Fraction fromBidens pilosacan Modulate the Differentiation of Helper T Cells and Prevent Autoimmune Diabetes in Non-Obese Diabetic Mice

Abstract: Compelling evidence suggests that infiltrating CD4+ type I helper T (Th1) cells in the pancreatic islets play a pivotal role in the progression of diabetes in non-obese diabetic (NOD) mice. We demonstrate in the present report that a butanol fraction of B. pilosa suppressed the development of diabetes, helped maintain levels of blood sugar and insulin in NOD mice in a dose-dependent manner and elevated the serum IgE levels regulated by Th2 cytokines in NOD mice. Moreover, the butanol fraction inhibited the dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
69
0
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 85 publications
(82 citation statements)
references
References 18 publications
5
69
0
8
Order By: Relevance
“…Accordingly, the butanol fraction of B. pilosa effectively prevented T1D in nonobese diabetic (NOD) mice [23]. Consistently, this prevention involved downregulation of Th1 cells or upregulation of Th2 cells.…”
Section: Antidiabetic Propertiesmentioning
confidence: 97%
See 4 more Smart Citations
“…Accordingly, the butanol fraction of B. pilosa effectively prevented T1D in nonobese diabetic (NOD) mice [23]. Consistently, this prevention involved downregulation of Th1 cells or upregulation of Th2 cells.…”
Section: Antidiabetic Propertiesmentioning
confidence: 97%
“…To test the immunomodulatory effect of B. pilosa , one study showed that B. pilosa extract and its butanol fraction could decrease Th1 cells and cytokines and increase Th2 cells and cytokines [23]. This study indicated that IC 50 value of the butanol fraction was 200  μ g/mL.…”
Section: Antidiabetic Propertiesmentioning
confidence: 99%
See 3 more Smart Citations